Comparison of Shear Bond Strength and Adhesive Remnant Index of Two Different Primers in Dry and Wet Conditions - Gurrala, Chaitanya; Mandapati, Surendra Reddy (The Journal of Dentists, 2023)
Purpose: To assess the shear bond strength (SBS) and adhesive remnant index score (ARI) of different primers in dry condition and in wet conditions. Materials and Methods: A total of 80 human premolars which are free from caries, cracks, and fine lines were collected and mounted on acrylic. These teeth were randomly distributed into two groups (Assure Plus and Transbond XT/MIP). Each group was again reassigned into two subgroups (dry and wet) with 20 teeth in each subgroup based on the primer used and enamel surface after etching (Contaminated or Non contaminated). All teeth bonded were then stored in separate glasses containing distilled water for seven days at 37 0C. Universal testing machine was used to measure the SBS by applying 50 kg of force at 0.5 mm/min. The adhesive remnant index was assessed by using a stereomicroscope. Results: There is no statistically significant difference in shear bond strength of Assure plus and Transbond XT bonded in dry conditions. Among the four subgroups, Assure Plus on wet teeth showed the high bond strength (12.63 ± 6.64 Mpa). There is a statistically significant difference in ARI scores between Assure Plus and Transbond MIP bonded in wet conditions (P<0.001). Conclusion: On moisture contaminated teeth, Assure Plus showed higher bond strength than Transbond MIP. Transbond MIP has the least bond strength among all, but the bond strength is adequate to withstand the masticatory forces.